Impact of DC-link fault on the dynamic performance of DFIG - Yunus, A.; Abu-Siada, Ahmed; Masoum, Mohammad Sherkat (IEEE, 2012)
The number of doubly fed induction generators (DFIG) connected to the existing network has increased significantly worldwide during the last two decades. This triggers off manufactures to improve the performance of DFIG through robust and reliable design. The stator in DFIG is directly connected to the grid whereas the rotor is interfaced to the grid through two voltage source converters; rotor side converter (RSC) and grid side converter (GSC), which are considered as the crux of the DFIG system. The converter stations determine the ability of wind turbine to operate optimally during wind speed fluctuation and it can provide reactive power support to the grid during grid disturbance events. The DC capacitor link between the two converters allows optimum and smooth power exchange between DFIG and the grid. Therefore, any faults within the DC link will affect the overall performance of the DFIG. This paper investigates the impact of open circuit and short circuit faults in the DC link capacitor on the dynamic performance of the DFIG. The compliance of the wind energy conversion (WEC) system with different grid codes such as those of Denmark, Spain, Nordic and Sweden under such faults is also investigated.